Association of the Host Immune Response with Protection Using a Live Attenuated African Swine Fever Virus Model - Carlson, Jolene; O’Donnell, Vivian; Alfano, Marialexia; Velazquez Salinas, Lauro; Holinka, Lauren G.; Krug, Peter W.; Gladue, Douglas P.; Higgs, Stephen; Borca, Manuel V. (My University, 2016)
African swine fever (ASF) is a lethal hemorrhagic disease of swine caused by a double-stranded DNA virus, ASF virus (ASFV). There is no vaccine to prevent the disease and current control measures are limited to culling and restricting animal movement. Swine infected with attenuated strains are protected against challenge with a homologous virulent virus, but there is limited knowledge of the host immune mechanisms generating that protection. Swine infected with Pretoriuskop/96/4 (Pret4) virus develop a fatal severe disease, while a derivative strain lacking virulence-associated gene 9GL (Pret4Δ9GL virus) is completely attenuated. Swine infected with Pret4Δ9GL virus and challenged with the virulent parental virus at 7, 10, 14, 21, and 28 days post infection (dpi) showed a progressive acquisition of protection (from 40% at 7 dpi to 80% at 21 and 28 dpi). This animal model was used to associate the presence of host immune response (ASFV-specific antibody and interferon (IFN)-γ responses, or specific cytokine profiles) and protection against challenge. With the exception of ASFV-specific antibodies in survivors challenged at 21 and 28 dpi, no association between the parameters assessed and protection could be established. These results, encompassing data from 65 immunized swine, underscore the complexity of the system under study, suggesting that protection relies on the concurrence of different host immune mechanisms.
Citation: Carlson, J.; O’Donnell, V.; Alfano, M.; Velazquez Salinas, L.; Holinka, L.G.; Krug, P.W.; Gladue, D.P.; Higgs, S.; Borca, M.V. Association of the Host Immune Response with Protection Using a Live Attenuated African Swine Fever Virus Model. Viruses 2016, 8, 291.
Keywords: Asf; Asfv; Immune Response